Intelligent Cloud Automation: A Framework for Enterprise-Scale Infrastructure Management - Suresh Kumar Maddali (Emerging Frontiers Library for The American Journal of Engineering and Technology, 2025)
Modern enterprises face critical challenges in managing cloud infrastructure at scale, where traditional manual approaches create bottlenecks that impede innovation and introduce operational risks. This article presents a comprehensive examination of an intelligent operations framework designed to address these challenges through serverless orchestration, automated discovery, and integrated governance mechanisms. The framework leverages event-driven architectures and infrastructure as code principles to transform infrastructure management from error-prone manual processes into automated, self-managing systems that deliver consistent outcomes across hybrid and multi-cloud environments. By embedding security and compliance capabilities throughout the automation platform rather than treating them as afterthoughts, the framework establishes comprehensive governance while maintaining operational agility. The article explores architectural foundations built on serverless technologies that minimize infrastructure overhead while maximizing scalability, dynamic asset discovery engines that maintain real-time inventory across distributed cloud environments, and modular workflow implementations spanning provisioning, maintenance, and access management. Integration with enterprise authentication systems ensures all automated actions remain properly authorized and auditable, while continuous compliance monitoring enables proactive remediation of policy violations. The framework incorporates sophisticated observability capabilities encompassing metrics, logs, and distributed traces to provide comprehensive visibility into both infrastructure health and automation performance. Through rigorous testing practices and careful orchestration of deployment phases, the framework balances security responsiveness with operational stability while addressing persistent challenges in identity management, configuration drift detection, and policy enforcement across heterogeneous cloud platforms.